PECULIARITIES OF STUDYING ENGLISH AND RUSSIAN DERIVATIONAL ELEMENTS THROUGH MEDIA TEXTS (Konferensiyalar | Conferences, 2024)
Word formation has always been a significant area of study for linguists. Its influence and effect spread to various field s of language, including advertisements. One of the most significant types of word formation is derivation. According to VinogradovV.V., the process of creating new words or new meanings with the help of prefix or suffix is called derivation (1960). This p henomenon in particular has been utilized as a tool for foregrounding in media texts. Its use varies from traditional forms to forms, which result in language deviations. Its role in attracting people’s attention and persuading them to purchase something h as been closely studied and developed throughout the history of linguistics.